2017
DOI: 10.4077/cjp.2017.baf476
|View full text |Cite
|
Sign up to set email alerts
|

The Modulative Effects of Microcurrent Electrical Nerve Stimulation on Diabetic Mice

Abstract: Diabetes (one of non-communicable diseases) is serious due to its complications, such like, cardiovascular ailments, neuropathy, nephropathy, retinopathy, wound gangrene and sexual impotence. Diabetes and associated chronic conditions are rapidly emerging as major health problems. In clinical, there were different drugs for diabetes treatment on different mechanisms. However, there were limited studies on the efficacy of electric stimulations on diabetes therapeutic application. In current study, we try to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…On the contrary, our study device exhibited good safety profile and is well tolerated by most patients. Furthermore, GV has been linked to several acute and chronic micro- and macro-vascular complications related to diabetes 10 , 22 24 . Whether the beneficial effects of TENS on MAGE reduction can be translated to amelioration of short and long-term diabetic complications as well as improvement in quality of life in patients with type 2 diabetes needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, our study device exhibited good safety profile and is well tolerated by most patients. Furthermore, GV has been linked to several acute and chronic micro- and macro-vascular complications related to diabetes 10 , 22 24 . Whether the beneficial effects of TENS on MAGE reduction can be translated to amelioration of short and long-term diabetic complications as well as improvement in quality of life in patients with type 2 diabetes needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study in STZ-induced diabetes mellitus in mouse models showed that microcurrent electrical nerve stimulation exhibited effects similar to anti-diabetic drugs, through the peroxisome proliferator-activated receptor (PPAR), bile secretion, and insulin signaling pathways 9 . In a pre-clinical setting, we have proven that our TENS device significantly improved glucose parameters in a diabetic mouse model 10 , as indicated by fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA 1c ) ( Appendix in Supplementary Material). Besides, TENS intervention reversed the pathological changes in liver, kidney, and pancreas in mice with diabetes mellitus induced by streptozotocin.…”
Section: Introductionmentioning
confidence: 98%
“…On the contrary, our study device exhibited good safety pro le and is well tolerated by most patients. Furthermore, GV has been linked to several acute and chronic micro-and macro-vascular complications related to diabetes 14,[25][26][27] . Whether the bene cial effects of TENS on MAGE reduction can be translated to amelioration of short and long-term diabetic complications as well as improvement in quality of life in patients with type 2 diabetes needs to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study in STZinduced diabetes mellitus in mouse models showed that microcurrent electrical nerve stimulation exhibited effects similar to anti-diabetic drugs, through the peroxisome proliferator-activated receptor (PPAR), bile secretion, and insulin signaling pathways 13 . In a pre-clinical setting, we have proven that our TENS device signi cantly improved glucose parameters in a diabetic mouse model 14 , as indicated by fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA 1c ). After a 6-week treatment period, FPG declined signi cantly in diabetic mice receiving TENS.…”
mentioning
confidence: 94%
“…Mice were fasted for 12 h and then orally administered 1.0 g of glucose per kg of body weight. The blood glucose from the blood samples (0.6 μL) collected at the indicated time points was measured using a glucometer (Accu-Chek ® ; Roche, Taipei, Taiwan) to determine plasma glucose concentration [22].…”
Section: Oral Glucose Tolerance Testmentioning
confidence: 99%